Pengaruh Corporate Social Responsibility Terhadap Tax Avoidance - Fandi Achmad Hidayat; Santi Novita (Politeknik Ganesha Medan, 2023)
This study aims to obtain empirical evidence about the effect of corporate social responsibility on tax avoidance. This study uses 114 observations or unbalanced panel data of non-financial industries listed on the Indonesia Stock Exchange for the years 2015-2019. The dependent variable in this study is tax avoidance which is measured using cash effective tax rate. The independent variable in this study is a corporate social responsibility as measured by the CSR index based on the GRI standard. This study also uses control variables consisting of company size, leverage, and return on assets. In addition, the analysis enriches with a comparison of tax avoidance among industries. Using Multiple Linear Regression and software STATA 14, the study's results indicate that corporate social responsibility has a positive effect on tax avoidance. This result support risk management theory. This research provides a sign not only for the government but also for investors to pay attention to tax avoidance practices primarily for the firms with a high rate of CSR activities.